A landmark-based geometric morphometric approach to quantify deviations from bilateral symmetry in polyplacophorans - Ramirez-Santana, Brenda Paola; Ospina-Garcés, Sandra Milena; Ramirez-Perez, Jorge Saul; Avila-Poveda, Omar Hernando (Zoologischer Anzeiger, 2023)
The class Polyplacophora (chitons) represents a dorsoventrally flattened mollusk group that has an oval-shaped body covered with eight overlapping sclerites providing bilateral symmetry. Chitons show abnormalities (teratologies) that are characterized by symmetry deviations between the right and left sides of their bodies. As these deviations do not result in damage that affects vital functions, chitons are able to reach adult stages. In this study, we quantify the asymmetric condition of the species Chiton articulatus using a landmark-based geometric morphometric approach to assess variation in shape and bilateral symmetry. A geometric configuration of 22 landmarks and 50 semi-landmarks was created to evaluate shape variation in abnormal and deformed specimens compared to normal Chiton articulatus specimens. Vectors of change in the body shape configurations of chitons indicate that the greatest change occurs in the anterior part of the body, with less change in the middle and posterior parts. This gives chitons a widened appearance and provides anatomic compensation to restore the bilateral symmetry of the body scleritome. The diverse abnormalities and deformities had little impact on shape variations and confirmed that the coalescence condition is an intermediate step between a normal condition and the abnormal conditions of hypomerism or hypermerism. The low levels of fluctuating asymmetry expressed in C. articulatus indicate that despite living in areas of high stress, such as the rocky intertidal coast, this species maintains stability in its development and shape. Our results can serve as a model for studying bilateral symmetry deviation in polyplacophorans.